2019
DOI: 10.26643/tjg.v8i8.8103
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Cigarette Smoking in Kenya and the Challenges Impeding Cessation

Abstract: Despite intense campaigns to minimize cigarette smoking owing to the socio-economic risks associated with it, cigarette smoking worldwide has continued to rise. This is a major concern to both public health authorities and medical practioners. This paper examines the Kenyan status on cigarette smoking through measurement of various parameters including mass media campaigns, taxation, level of education, nature of employment, and government legislation. Descriptive research design was employed because of its ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Likewise, results from a study conducted in rural settings in Uganda found similarly found that people with any education level were less tobacco smoking than people without any form of education level (14). In contrast, results from a study conducted in Kenya, people who attained high school education level and above were likely to smoke more than people with lower education level (23).Tobacco smoking by education level differs from a region to another but it decrease globally with the level of education. The difference between tobacco use in different countries…”
Section: Discussionmentioning
confidence: 94%
“…Likewise, results from a study conducted in rural settings in Uganda found similarly found that people with any education level were less tobacco smoking than people without any form of education level (14). In contrast, results from a study conducted in Kenya, people who attained high school education level and above were likely to smoke more than people with lower education level (23).Tobacco smoking by education level differs from a region to another but it decrease globally with the level of education. The difference between tobacco use in different countries…”
Section: Discussionmentioning
confidence: 94%